Research in times of COVID-19 - Liu, Yuyu (Bellaterra : journal of teaching & learning language & literature, 2021)
Cristina Aliagas, Júlia Llompart, Mariona Pascual, Naymé Salas and Claudia Vallejo are Early Career Researchers in the Department of Language and Literature Education and Social Science Education at the Universitat Autònoma de Barcelona. In this interview they were asked to reflect on their experiences as researchers in times of the COVID-19 pandemic.